Reconstruction of rational ruled surfaces from their silhouettes. (May 2021) - Gallet, Matteo; Lubbes, Niels; Schicho, Josef; Vršek, Jan
Abstract: We provide algorithms to reconstruct rational ruled surfaces in three-dimensional projective space from the "apparent contour" of a single projection to the projective plane. We deal with the case of tangent developables and of general projections to P 3 of rational normal scrolls. In the first case, we use the fact that every such surface is the projection of the tangent developable of a rational normal curve, while in the second we start by reconstructing the rational normal scroll. In both instances we then reconstruct the correct projection to P 3 of these surfaces by exploiting the information contained in the singularities of the apparent contour.